ChemInform Abstract: Synthesis, Characterization and the Suzuki—Miyaura Coupling Reactions of N‐Heterocyclic Carbene—Pd(II)—Pyridine (PEPPSI) Complexes. Issue 22 (15th May 2015) - Yasar, Sedat; Sahin, Caglar; Arslan, Murat; Oezdemir, Ismail
Abstract: A series of new air and moisture‐stable PEPPSI complexes are developed and evaluated for their catalytic performance in Suzuki cross‐coupling reactions.